COMPARATIVE STUDY OF BIODIESEL FROM KERNEL OILS OFJATROPHA CURCAS AND AZADIRACHTA INDICA IN ZARIA NIGERIA. (2011) - M, M; GARBA, GARBA; M.A, M.A; NOSIRI, CHIDI; , A.A. AUDU; ABDULJALAL, ABDULJALAL; D, D
No abstract available